Effects of Salinity on Growth, Water Relations and Photosynthetic Rate of Tomatoes Grown in Nutrient Film Technique - Ismail, Mohd Razi; Burrage, S. W. (Universiti Putra Malaysia Press, 1994)
Tomato (Lycopersicon esculentum Mill. var Counter) plants were grown under different salinity conditions using the Nutrient Film Technique (NFT). In the first experiment, plants were exposed to salinities of 2.5 , 5.5 and 8.5 mS cm-l . In the second experiment, plants were exposed to continuous salinity of 2.5 and 8.5 mS cm-l and altered salinity i. e low to high or vice versa. Leaf and stem dry weight were markedly reduced when plants were exposed to continuous salinity of 8.5 mS cm-l. Exposure to high salinity at the later stages of growth also resulted in the reduction of leaf dry weight to a level similar to that of plants exposed to continuous high salinity. This could be attributed to the restriction in the movement of water within the plants as indicated by the reduction in plant water uptake and leaf water potential. Photosynthetic rate was not affected although stomatal conductance and leaf water potential were reduced when plants were exposed to high salinity.